Non-surgical endodontic treatment of mandibular left second premolar with gemination: a case report - Banomyong, Danuchit; Kamolroongwarakul, Roongrawee (Thai Endodontic Journal, 2022)
Objective: This case report describes a non-surgical endodontic treatment of mandibular left second premolar with gemination that had carious exposed pulp. Case report: In Thai male patient aged 35 years old, clinical examination, periapical radiographs at different horizontal angles and cone-beam computed tomography (CBCT) were performed to investigate unusual anatomy of coronal structure and root canal system in mandibular left second premolar with gemination. The gemination tooth had one large pulp chamber and two separated root canals, which were then joined at the apical third of root, with a presence of incomplete isthmus. After caries removal, non-surgical endodontic treatment was performed under a consideration of unusual root canal system. Coronal access was modified following the anatomy of large pulp chamber. Mesial and distal root canals were located and instrumented with rotary Ni-Ti files (Twisted Files, Sybron Endo, Orange, CA, USA) with copious amount of irrigants and passive ultrasonic irrigation technique. Combination of lateral and warm vertical compaction, as a hybrid technique, was used to obtain three-dimensional obturation in the unusual root canal system. A prefabricated fiber post and resin composite core build-up restoration was placed as an intermediate restoration. The patient was recalled to evaluate the successful outcome of treatment. Conclusion: With a specific consideration of unusual root canal anatomy, geminated mandibular second premolar with pulpal and periapical pathosis can be successfully treated by non-surgical endodontic treatment.